Introducing a new tool for greenhouse gas calculation tailored for cropland: rationale, operational framework and potential application - R. Wassmann; R. Pasco; J. Zerrudo; D. M. Ngo; T. B. T. Vo; B. O. Sander (Carbon Management, 2019)
The new GHG calculator named SECTOR (Source-selective and Emission-adjusted GHG CalculaTOR for Cropland) is based on the IPCC Tier 2 approach for rice as well as other crops. The new features of SECTOR facilitate high flexibility in terms of entering newly obtained emission factors, easy data transfer from crop statistics for entering activity data and detailed specifications of GHG scenarios. A new procedure of entering frequency-based data on current water management practices was also developed. Moreover, the tool allows deviating from the 2006 IPCC Guidelines by considering field records with high background levels of N2O emissions in the overall assessment of GHG emissions. This article assesses different applications of the tool, namely as add-ons to field measurements, for GHG calculation at national/sectorial scale and within measurement, reporting and verification of development projects. SECTOR is downloadable in the form of templates that can be used to develop custom versions with varying levels of disaggregated data entries at different scales. A case study for rice production in one Vietnamese province demonstrates the potential to display GHG results in combination with GIS. SECTOR can easily be adjusted to incorporate new emission factors and calculation procedures expected in forthcoming revisions of the IPCC Guidelines.Highlights A new GHG calculation tool was developed based on the IPCC Tier 2 approach for rice as well as other crops Features of the tool facilitate high flexibility in terms of emission factors, easy data transfer from crop statistics for entering activity data and detailed specification of GHG scenarios This article assesses different user groups and possible applications of the tool A case study for rice production in one Vietnamese province demonstrates the potential to display GHG results in combination with GIS